Excess non-COVID-19 mortality in Portugal: seven months after the first death. - Vieira,André (2020)
Abstract Background: On March 16, 2020, the first death from COVID-19 was recorded in Portugal. Since then, there has been a reorganization of health services, changing the normal approach for the different cases of public health. Excess deaths recorded without a COVID-19 diagnosis are called excess mortality without COVID-19 (EM non-COVID-19). This study aims to estimate the EM non-COVID in the 7-month period after the first registered Covid-19 death. Methods: The following 2 methods were used to estimate the excess mortality in this period: the daily historical average of reported deaths and an adapted auto regressive integrated moving average (ARIMA) model, considering the previous 5 years of records until October 16. For this model, after March 16, data was replaced with the daily historical average deaths from the previous 5 years, simulating the closest scenario possible as there was no pandemic. Only deaths from natural causes were selected for these estimations. For EM non-COVID-19 estimation, we subtracted the COVID-19 deaths from the overall excess mortality. Results: Between March 16, 2020, and October 16, 2020, there was an excess of 6,330 deaths from natural causes, i.e., nearly 12% more than expected. Both methods estimated an EM non-COVID-19 of around 66-67% in this period, with a greater relevance in mid-July and mid-September. Conclusions: Excess mortality was present almost every day during the study period. EM non-COVID-19 seemed to vary over time, showing some inadequacy of healthcare services in management of other patients free of COVID-19 in Portugal during periods with a greater patient volume. It is necessary to take care and monitor COVID-19 cases but also non-COVID-19 cases.